The Post-Coloniality of 'Coming of the dry Season' - Javangwe, Tasiyana D. (Prestige Books, 2016)
The term 'post-colonial' evokes 'powerful contending forces and disputes' as to whether it refers to 'texts or practices, to psychological conditions or concrete historical processes', or perhaps to the interplay of all these (Mongia, 1996:1). Scholars of the postcolonial discourse have raised concerns over implications of periodicity carried by the term `postcolonial' . Ella Shohat complains that the residual meaning of periodity in the 'post' of postcolonial implies that the colonial period is seen as having been followed by a 'post,' as in after colonialism. While there is no question that the colonial relations were fundamentally shaken by struggles for freedoms, overemphasis on 'post' does not suggest that the legacies of Colonialism have been totally done away with. This narrow understanding of post-coloniality it de-emphasises 'neocolonial global positionings' (Shohat, 1996, (324). Padmini Mongia adds to this critique of the term post-colonial as it directs attention away from present inequalities- political, economic, and discursive- in the global system' (Mongia, 1996, :1). This essay will therefore attempt to take a different approach and refuses to imprison itself within the surface implications of periodicity carried in the term 'post-colonial'. The post-colonial identities are instead perceived as inhabiting all periods from the time of enlightenment to the period after effective de-colonisation.